Electricity - Twist, Clint (New York : Bearport Pub., 2006)
Presents a children's book for early readers that describes what electricity is, where it comes from, and how it is used to make heat and light.
Includes index.
Library Media Connection starred.
3.5
K-3
Keywords: Electricity -- Juvenile literature; Electricity; Electricity